Gomphrena claussenii, the first South-American metallophyte species with indicator-like Zn and Cd accumulation and extreme metal tolerance - Villafort Carvalho, Mina Tomaz; Amaral, Douglas C.; Guilherme, Luiz R. G.; Aarts, Mark G. M. (Frontiers in Plant Science, 2013)
Plant species with the capacity to tolerate heavy metals are potentially useful for phytoremediation since they have adapted to survive and reproduce under toxic conditions and to accumulate high metal concentrations. Gomphrena claussenii Moq., a South-American species belonging to the Amaranthaceae, is found at a zinc (Zn) mining area in the state of Minas Gerais, Brazil. Through soil and hydroponic experiments, the metal tolerance and accumulation capacities of G. claussenii were assessed and the effects on physiological characteristics were compared with a closely-related non-tolerant species, Gomphrena elegans Mart. Gomphrena. claussenii plants grown in soil sampled at the Zn smelting area accumulated up to 5318 µg g-1 of Zn and 287 µg g-1 of Cd in shoot dry biomass after 30 days of exposure. Plants were grown in hydroponics containing up to 3000 µM of Zn and 100 µM of Cd for G. claussenii and 100 µM of Zn and 5 µM of Cd for G. elegans. Gomphrena claussenii proved to be an extremely tolerant species to both Zn and Cd, showing only slight metal toxicity symptoms at the highest treatment levels, without significant decrease in biomass and no effects on root growth, whereas the non-tolerant species G. elegans showed significant toxicity effects at the highest exposure levels. Both species accumulated more Zn and Cd in roots than in shoots. In G. elegans over 90% of the Cd remained in the roots, but G. claussenii showed a root:shoot concentration ratio of around 2, with shoots reaching 0.93 % Zn and 0.13 % Cd on dry matter base. In G. claussenii shoots, the concentrations of other minerals, such as Fe and Mn, were only affected by the highest Zn treatment while in G. elegans the Fe and Mn concentrations in shoots decreased drastically at both Zn and Cd treatments. Taking together, these results indicate that G. claussenii is a novel metallophyte, extremely tolerant of high Zn and Cd exposure and an interesting species for further phytoremediation studies.